Transformative Shifts: From Puritanical Rigidities to Cosmopolitan Flexibilities in Islamic Education - Suhaimis, Suhaimis; Amrizon, Amrizon (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This journal explores the evolving dynamics within Islamic educational paradigms in the context of increasing global interconnectedness. The study investigates the transition from rigid, puritanical educational models, which emphasize strict adherence to traditional interpretations and practices, towards more flexible, cosmopolitan approaches that accommodate diversity, inclusivity, and global perspectives. Through a comprehensive literature review and qualitative analysis of case studies from various Islamic educational institutions worldwide, the research identifies key factors driving this shift. These include the influence of globalization, advancements in information and communication technologies, and the growing recognition of the need for educational systems that prepare students for the complexities of a pluralistic world. The article argues that embracing cosmopolitan flexibility in Islamic education does not necessitate the abandonment of core religious values. Instead, it advocates for a balanced approach that integrates traditional Islamic teachings with contemporary pedagogical methods and curricula that promote critical thinking, intercultural understanding, and ethical reasoning. By highlighting successful examples of transformative educational practices, the study aims to provide a framework for policymakers, educators, and scholars to develop and implement educational models that reconcile the rich heritage of Islamic knowledge with the demands of modern, globalized societies. The findings suggest that such an approach not only enhances the quality and relevance of Islamic education but also fosters a more inclusive and cohesive global Muslim community.